GENETIC POLYMORPHISM OF ALDEHYDE DEHYDROGENASE 2 (ALDH2) OF MINANGKABAU ETHNIC GROUP - Hidayat, Taufik; Nurhantari, Yudha; Suhartini, . (E-Jurnal Medika Udayana; Vol 12 No 6 (2023): E-Jurnal Medika Udayana, 2023)
Introduction.  Aldehyde dehydrogenase 2 (ALDH2) is the main isozymes that can converted efficiently acetaldehyde into acetic acid. The aim of this study is to analyze genetic polymorphism of ALDH2 of Minangkabau ethnic group and its relationship with alcohol sensitivity. Methode.  This research use descriptive methodology. Population and sample taken from Minangkabau people who lived in Yogyakarta who passed the inclusion and exclusion criteria. Examination of polymorphism of ALDH2 was conducted to the sample with PCR-RFLP with Ear! Restriction enzyme. Results.  From 24 electrophoresis samples we got genotype frequency of wild type is 5 samples (20.8%), heterozygote polymorphism is 16 samples (66.7%) and homozygote polymorphism/polymorphic type is 3 samples (12.5%). Conclusion.  We conclude that there are heterozygote polymorphism and homozygote polymorphism in the young adult, non alcoholic and healthy Minangkabau ethnic group. Keywords:  aldehyde dehydrogenase 2, polimorphism, Minangkabau ethnic